Biological Activities of In-House Developed Haloxylon griffithii Plant Extract Formulations - Shagufta Kamal; Ismat Bibi; Kanwal Rehman; Ameer Fawad Zahoor; Amna Kamal; Fatima Aslam; Fatmah Ali Alasmary; Tahani Mazyad Almutairi; Hassna Mohammed Alhajri; Siham A. Alissa; Hafiz M. N. Iqbal (Plants, 2021)
The therapeutic potential of whitish glaucous sub-shrub Haloxylon griffithii (H. griffithii), abundantly present in southern regions of South Asia, has been neglected. The current study aimed to assess the phytochemicals and pharmacological potential of native and gemm forms of H. griffithii. Results of antimicrobial activity revealed that all tested bacteria were susceptible at concentrations ≤50 µg/mL, while tested fungal species were susceptible at ≤25 µg/mL. The values of minimum bactericidal concentrations (MBCs) ranged between 10.75 ± 0.20 to 44.25 ± 0.42 µg/mL, 8.25 ± 0.02 to 28.20 ± 0.80 µg/mL. The value of minimum inhibitory concentration (MIC) of all microbial species was ≤100 µg/mL and the antibiotic mechanism showed that both extracts were highly bactericidal and fungicidal. Results of average log reduction of viable cell count in time kill assay indicated that Pseudomonas aeruginosa (P. aeruginosa) NCTC 1662, Candida albicans (C. albicans) IBL-01, Candidakrusei (C. krusei) ATCC 6258, and Aspergillus flavus (A. flavus) QC 6158 were the most susceptible microbial species. High performance liquid chromatography (HPLC)-based quantification confirmed the presence of gallic acid p.coumeric acid catechin, vanillin, ellagic acid, and salicylic acid, while in native extract only gallic acid. Native and gemm extracts exhibited excellent radical scavenging potential measured by 1,1-diphenyl-2-picryl-hydrazyl radical scavenging assay. Significant thrombolytic activity was found in both extracts with negligible haemolytic activity. Highest percent (%) clot lysis was observed with gemm extracts (87.9 ± 0.85% clot lysis). In summary, we infer that valuable evidence congregated can be exploited for better understanding of gemm H. griffithii’s health benefits, further, to increase its utility with enriching dietary sources of health-promoting compounds.